1993
DOI: 10.1123/ssj.10.3.241
|View full text |Cite
|
Sign up to set email alerts
|

The Unequal Opportunity for Equal Ability Hypothesis: Racism in the National Football League?

Abstract: This paper examines race equality within the labor market of professional football, specifically addressing the issue of whether NFL team management discriminates against marginal nonwhite players. To examine this, we compared the racial proportions of “protected” players to proportions of players designated as “Plan B” free agents. We considered Plan B players as “marginals” from management’s viewpoint. Our hypothesis that these athletes would be disproportionately white was confirmed. Reasons for the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Berghorn (1988, 1993) demonstrated that while black athletes had made inroads into central positions in collegiate basketball, this progress was due mostly to the huge increases in the number of black athletes participating and was not proportional to the numbers of new athletes entering the sport. Stacking still exists in women's collegiate volleyball (Eitzen and Fürst 1989), professional baseball (Smith and Seff 1989;Lavoie and Leonard 1994) and professional (Schneider and Eitzen 1987;Kooistra, Mahoney and Bridges 1993) and collegiate (Jones et al 1987;Lewis 1995) football. These studies suggest that while many black athletes have achieved notoriety and success in the white-dominated forum of sport, racial stereotypes of minorities' supposed lack of leadership and intellectual qualities still flourish.…”
Section: Theorymentioning
confidence: 96%
“…Berghorn (1988, 1993) demonstrated that while black athletes had made inroads into central positions in collegiate basketball, this progress was due mostly to the huge increases in the number of black athletes participating and was not proportional to the numbers of new athletes entering the sport. Stacking still exists in women's collegiate volleyball (Eitzen and Fürst 1989), professional baseball (Smith and Seff 1989;Lavoie and Leonard 1994) and professional (Schneider and Eitzen 1987;Kooistra, Mahoney and Bridges 1993) and collegiate (Jones et al 1987;Lewis 1995) football. These studies suggest that while many black athletes have achieved notoriety and success in the white-dominated forum of sport, racial stereotypes of minorities' supposed lack of leadership and intellectual qualities still flourish.…”
Section: Theorymentioning
confidence: 96%
“…1. Kooistra, Mahoney, and Bridges (1993) also find evidence that White players were disproportionately rewarded with regard to their contract status compared with African Americans in the NFL.…”
Section: Notesmentioning
confidence: 71%
“…Research examining race and football participation around 1993 indicates that 44% of Division I college football players were Black 2 . Additional research indicated that only about 40% of NFL players were white 3 . These percentages, combined with historical census data, make it reasonable to argue that white persons would fill only half of the contemporary NFL head coaching positions if the playing field were level.…”
Section: Taskmentioning
confidence: 99%